Arbuscular mycorrhizal fungi enhance disease resistance of Salvia miltiorrhiza to Fusarium wilt - Pu, Chunjuan; Ge, Yang; Yang, Guang; Zheng, Han; Guan, Wei; Chao, Zhi; Shen, Ye; Liu, Sha; Chen, Meilan; Huang, Luqi (Frontiers in Plant Science, 2022)
Salvia miltiorrhiza Bunge (Danshen in Chinese) is vulnerable to Fusarium wilt, which severely affects the quality of the crude drug. Mycorrhizal colonization enhances resistance to fungal pathogens in many plant species. In this study, pre-inoculation of S. miltiorrhiza with the arbuscular mycorrhizal fungi (AMF) Glomus versiforme significantly alleviated Fusarium wilt caused by Fusarium oxysporum. Mycorrhizal colonization protected S. miltiorrhiza from pathogen infection, thereby preventing a loss of biomass and photosynthesis. There were greater defense responses induced by pathogen infection in AMF pre-inoculated plants than those in non-treated plants. AMF pre-inoculation resulted in systemic responses upon pathogen inoculation, including significant increases in the protein content and activities of phenylalanine ammonia-lyase (PAL), chitinase, and β-1,3-glucanase in S. miltiorrhiza roots. In addition, mycorrhizal pre-inoculation caused upregulation of defense-related genes, and jasmonic acid (JA) and salicylic acid (SA) signaling pathway genes after pathogen infection. The above findings indicate that mycorrhizal colonization enhances S. miltiorrhiza resistance against F. oxysporum infection by enhancing photosynthesis, root structure, and inducing the expression of defense enzymes and defense-related genes on the other hand.